Application of integrated traditional Chinese and western medicine nursing in rehabilitation of patients with hemiplegia after ischemic stroke (中西医结合护理干预在缺血性脑卒中偏瘫患者康复中的应用) - HUANG Chaoping (黄朝萍); WANG Li (王丽); LI Yanmin (李艳敏); ZHANG Shuai (张帅); CHENG Jiangyan (程江艳); WANG Jing (王晶); QIU Yajiao (邱亚娇); LIANG Hui (梁慧) (Association of Integrative Nursing, 2021)
Objective To investigate the effect of integrated traditional Chinese and western medicine nursing in rehabilitation of patients with hemiplegic patients after ischemic stroke. Methods A total of 126 patients with hemiplegia after ischemic stroke were selected. According to the method of random number table, they were divided into control group and observation group, with 63 cases in each group. All patients received conventional drug treatment, routine care and rehabilitation training, and those in the observation group were given integrated traditional Chinese and western medicine nursing interventions. The Fugl-Meyer Assessment (FMA) scale and Brathel Index were measured and compared between two groups. The effect of rehabilitation nursing was evaluated by self-made rating scale. Results The scores of FMA and BI increased in both two groups after intervention, and scores of FMA and BI in the observation group were higher than those in the control group (P＜0. 01). The score for effect evaluation of nursing intervention in the observation group was higher than that in the control group (P＜0. 01). Conclusion In the early rehabilitation of hemiplegic patients after ischemic stroke, the use of integrated traditional Chinese and Western medicine nursing can improve the recovery and quality of life of patients. (目的 观察中西医结合护理干预在缺血性脑卒中偏瘫患者康复中的应用的效果。方法 选取126例缺血性脑卒中偏瘫患者为研究对象, 按照随机数字表分为对照组和观察组, 各63例。2组均接受药物治疗, 对照组接受常规护理和康复训练指导, 观察组在对照组的基础上实施早期中西医结合护理干预。对比干预前和干预后2组Fugl-Meyer运动功能量表(FMA)评分和Barthel指数(BI)评定结果, 评价护理效果。结果 干预后, 2组FMA量表评分和BI评分均较干预前上升, 且观察组FMA量表评分和BI评分高于对照组, 差异有统计学意义(P＜0. 01)。观察组护理效果评价得分高于对照组, 差异有统计学意义(P＜0. 01)。结论 缺血性脑卒中偏瘫患者早期康复中实施中西医结合护理干预, 可以促进患者运动功能康复, 提高患者生活质量。)